The interestings - Wolitzer, Meg (Riverhead Books, 2013)
The kind of creativity that is rewarded at age fifteen is not always enough to propel someone through life at age thirty; not everyone can sustain, in adulthood, what seemed so special in adolescence. The summer that Nixon resigns, six teenagers at a summer camp for the arts become inseparable. The friendships endure and even prosper, but also underscore the differences in their fates, in what their talents become and the shapes their lives take.